About Enlivening on Stage and Potentials of the Autobiographical Archive Illustrated by Selected Croatian Theatrical Performances - Abrasowicz , Gabriela (Poznańskie Studia Slawistyczne, 2020)
Autobiographism has been noticeably conquering the Croatian theatre which results in specific artistic projects, mainly falling into the category of theatre of the real. This material calls for a description of strategies, functions and potentials. The most important here is the freedom to (re)construct identity – performativity – communication and interaction. The styling of an autobiographical archive and its extension into action allows adopting a new view and interpreting historical events and current social problems differently. This phenomenon is manifested in selected performances which involve staging a dramatic text, adapting prose or journalistic text, compiling and processing various cultural texts, incorporating the performers’ confessions and observations, and developing documentary material. Descriptions of the latest performances confirm reactivity of the theatre, its power to concertize and subjectivize, as well as to model the audience’s attitudes.